Interleukin-10 induces interferon-γ-dependent emergency myelopoiesis - Cardoso, A (2021)
In emergency myelopoiesis (EM), expansion of the myeloid progenitor compartment and increased myeloid cell production are observed and often mediated by the pro-inflammatory cytokine interferon gamma (IFN-γ). Interleukin-10 (IL-10) inhibits IFN-γ secretion, but paradoxically, its therapeutic administration to humans causes hematologic changes similar to those observed in EM. In this work, we use different in vivo systems, including a humanized immune system mouse model, to show that IL-10 triggers EM, with a significant expansion of the myeloid progenitor compartment and production of myeloid cells. Hematopoietic progenitors display a prominent IFN-γ transcriptional signature, and we show that IFN-g mediates IL-10-driven EM. We also find that IL-10, unexpectedly, reprograms CD4 and CD8 T cells toward an activation state that includes IFN-γ production by these T cell subsets in vivo. Therefore, in addition to its established anti-inflammatory properties, IL-10 can induce IFN-γ production and EM, opening additional perspectives for the design of IL-10-based immunotherapies.